Clinical course of ectopic pregnancy:a tertiary centre experience - J. C., Spandana; D., Tejaswini; Bai, G. Sunanda (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Ectopic pregnancy (EP) is one of the causes of maternal mortality and morbidity in the first trimester. EP is still a major challenge and its incidence is on the rise due to changes in lifestyle and advances in medical practice. The early diagnosis and treatment of this condition over the past two decades has allowed a definitive medical management of unruptured ectopic pregnancies even before there were clinical symptoms in these high-risk women. Methods: It was a retrospective study of 100 cases of EP conducted in the Department of Obstetrics and Gynecology, Bowring and Lady Curzon Hospital, attached to Bangalore medical college, Bengaluru for a period of 3 years. The aim of the study was to study the incidence, risk factors, clinical profile and management of EP cases. Results: Incidence of EP was 1.3% of all deliveries and 5.6% of gynecological surgeries. Peak age group was between 25-30 years (37%). Most of them were multiparous (83%), 58% of the patients had identifiable risk factors. 95% had amenorrhea, followed by pain abdomen in 81%, bleeding PV in 43%. 17% presented with shock. 91% patients presented with ruptured ectopic, 9% were unruptured. Unruptured cases were treated medically using Methotrexate. Laparotomy was done for ruptured cases. Commonest site of Ectopic was ampulla (81%). Salpingectomy was done for most cases (86%). No maternal mortality observed. Conclusions: All high-risk women should be screened at the earliest with serum β-hCG and TVS. The impact on future fertility can be improved by focusing on primary prevention and early diagnosis before rupture.